(untitled) (University of Khartoum Engineering Journal, 2022)
The main objective of this paper is to study the influence of placement and intrinsic parameters on swellingpressure and evaluate factors combining intrinsic and placement parameters for its prediction. The expansive soilsamples were collected, from Alfao in Eastern Sudan (Soil 1) and Abeyi in Southern Kordofan (Soil 2). Soil 1 has avery high swelling potential whereas Soil 2 has a moderate potential for swelling. The basic soil properties weremeasured and the suction moisture content relationship was determined for the two soils using the filter paper method.Statically compacted specimens with different initial moisture contents and different dry densities were prepared in theOedometer ring. The swelling pressure of the two soils was accurately measured using the constant volume method.The test results have shown that there is a direct linear relationship between swelling pressure and dry density.Excellent relationship exists between swelling pressure and soil suction. The relationship between swelling pressureand liquidity Index is excellent for the tested soils when the samples are prepared at the same dry density. A newfactor, soil consistency factor (Fc) which is a combination of the consistency index CI, dry density and void ratio isintroduced. The factor combines intrinsic and placement parameters. Very good relationship was found betweenswelling pressure and Fc for the same soil. This factor could be used for the prediction of the swelling pressure ofcompacted soils with excellent results when the water content is low